Ceramics with the signature of wood: a mechanical insight. (January 2020) - Bigoni, D.; Cavuoto, R.; Misseroni, D.; Paggi, M.; Ruffini, A.; Sprio, S.; Tampieri, A.
Abstract: In an attempt to mimic the outstanding mechanical properties of wood and bone, a 3D heterogeneous chemistry approach has been used in a biomorphic transformation process (in which sintering is avoided) to fabricate ceramics from rattan wood, preserving its hierarchical fibrous microstructure. The resulting material (called biomorphic apatite ​[BA] henceforth) possesses a highly bioactive composition and is characterised by a multiscale hierarchical pore structure, based on nanotwinned hydroxyapatite lamellae, which is shown to display a lacunar fractal nature. The mechanical properties of BA are found to be exceptional (when compared with usual porous hydroxyapatite and other ceramics obtained from wood through sintering) and unique ​as they occupy a zone in the Ashby map previously free from ceramics, but not far from wood and bone. Mechanical tests show the following: (i) the strength in tension may exceed that in compression, (ii) failure in compression involves complex exfoliation patterns, thus resulting in high toughness, (iii) unlike in sintered porous hydroxyapatite, fracture does not occur 'instantaneously, ' ​but its growth may be observed, and it exhibits tortuous patterns that follow the original fibrillar structure of wood, thus yielding outstanding toughness, (iv) the anisotropy of the elastic stiffness and strength show unprecedented values when situations of stresses parallel and orthogonal to the main channels are compared. Despite being a ceramic material, BA displays a mechanical behavior similar on the one hand to the ligneous material from which it was produced (therefore behaving as a 'ceramic with the signature of wood') and on the other hand to the cortical/spongy osseous complex constituting the structure of compact bone.